The effect of wet compost extract on the root tubers of green pea - Fehér, Bernadett; Demeter, Ibolya; Aranyos, Tibor; Tomócsik, Attila; Makádi, Mariann (Acta Agraria Debreceniensis, 2017)
Nitrogen plays significant role in the life of plants, it could be the main limiting factor of plant growth. Sustainable plant nutrition pays attention to satisfy the plants’ nutrient demand without chemical fertilizers, e.g. by bounding the atmospheric nitrogen. The nitrogen fixing organizations play important role in supplying plants with nitrogenbecause the N2-fixingbacteria can fix high amounts of nitrogen.Many effects of the sewage sludge compost extracts is known in the literature. We studied the effect of sewage sludge compost water extract in laboratory conditions on the growth of Rhizobium spp. isolated from green pea, while in a small plot experiment thepea-Rhizobium symbiosis were studied on sandy soil in the Nyírség region. The extract was produced under aerobic conditions. The compost extract was applied before and/or after sowing. In the laboratory experiments we used the sterile version of extract, in different doses.In our work we present the effect of compost water extract on the number of green pea roots nodules, dry weight of the plant and reproduction of the Rhizobium bacteria.